2003
DOI: 10.1038/sj.bjp.0705223
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk between presynaptic angiotensin receptors, bradykinin receptors and α2‐autoreceptors in sympathetic neurons: a study in α2‐adrenoceptor‐deficient mice

Abstract: 1 In mouse atria, angiotensin II and bradykinin lose much or all of their noradrenaline release-enhancing effect when presynaptic a 2 -autoinhibition does not operate either because of stimulation with very brief pulse trains or because of treatment with a 2 antagonists. We now studied this operational condition in a 2 -adrenoceptor-deficient mice. Release of 3 H-noradrenaline was elicited by electrical stimulation. 2 In tissues from wild-type (WT) mice, angiotensin II and bradykinin increased the overflow of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 30 publications
(67 reference statements)
2
20
0
1
Order By: Relevance
“…It has been shown that on-going α 2 AR-signaling markedly enhanced the stimulating effect of the angiotensin AT1 receptor (AT 1 R) – phospholipase C – protein kinase C (PKC) pathway on norepinephrine release in the rat vas deferens (Talaia et al, 2006). Similarly, studies on tissues from genetically modified mice (Trendelenburg et al, 2003a) demonstrated that the enhancing effect of release-stimulating receptors, including the AT 1 R, depended on active α 2 AR-signaling. However, the interaction involved the α 2C AR-subtype only (Figure 1).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…It has been shown that on-going α 2 AR-signaling markedly enhanced the stimulating effect of the angiotensin AT1 receptor (AT 1 R) – phospholipase C – protein kinase C (PKC) pathway on norepinephrine release in the rat vas deferens (Talaia et al, 2006). Similarly, studies on tissues from genetically modified mice (Trendelenburg et al, 2003a) demonstrated that the enhancing effect of release-stimulating receptors, including the AT 1 R, depended on active α 2 AR-signaling. However, the interaction involved the α 2C AR-subtype only (Figure 1).…”
Section: Introductionmentioning
confidence: 95%
“…AT 1 R-G q -signaling stimulates norepinephrine release by interfering with the down-stream signaling of G i (Cox et al, 2000). The AT 1 R/α 2 AR interaction involved only the α 2C - and not the α 2A -subtype (Trendelenburg et al, 2003a). The present results show that α 2C AR-stimulation or AT 1 R-inhibition was required for α 2A AR to effectively moderate peripheral norepinephrine release in SHR during tyramine-stimulated norepinephrine release.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, and since the evidence supporting the view that there are AT 1A and AT 1B subtypes with pharmacological expression rely on differences between pre-and postjunctional AT 1 receptors, the comparison of the receptors mediating the prejunctional facilitation of noradrenaline with those mediating the postjunctional effect of angiotensin II will constitute the nuclear message of this review. The facilitation of noradrenaline release caused by angiotensin II -which is apparently mediated by AT 1B -receptors -requires an ongoing a 2 -autoinhibition (some degree of tonic autoinhibition) since the blockade of a 2 -autoreceptors prevents the effect of angiotensin II [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…It is known that α-ARs could interact with other receptor systems in ways that are receptor-specific. For example, in mouse atria, angiotensin and bradykinin receptors interact with α 2 -AR (Cox et al, 2000;Trendelenburg et al, 2003) and protein kinase C activation plays a role in this functional interaction (Mota and Guimaraes, 2003). More detailed experiments are necessary to determine whether or not there is direct coupling of α 1 -and α 2 -ARs or if post receptor events are responsible for the functional interaction in veins.…”
Section: Functional Interaction Between α 1 -And α 2 -Arsmentioning
confidence: 99%